2021
DOI: 10.1161/circresaha.121.319587
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and Lymphatic Malformations: Perspectives From Human and Vertebrate Studies

Abstract: Vascular malformations, affecting ≈1% to 1.5% of the population, comprise a spectrum of developmental patterning defects of capillaries, arteries, veins, and/or lymphatics. The majority of vascular malformations occur sporadically; however, inherited malformations exist as a part of complex congenital diseases. The malformations, ranging from birthmarks to life-threatening conditions, are present at birth, but may reveal signs and symptoms—including pain, bleeding, disfigurement, and functional defects of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Nowadays, another classification was added to this widely used classification, according to the microscopic aspect: lymphangioma simplex (lymphangioma circumscriptum ), characterized by the presence of thin-walled lymphatic vessels; cavernous lymphangioma, characterized by dilated lymphatic vessels; cystic lymphangioma (CH), with huge, macroscopic lymphatic spaces; and benign acquired progressive lymphangioma, in which the lymphatic channel dissects the dense collagen bundles [ 27 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Nowadays, another classification was added to this widely used classification, according to the microscopic aspect: lymphangioma simplex (lymphangioma circumscriptum ), characterized by the presence of thin-walled lymphatic vessels; cavernous lymphangioma, characterized by dilated lymphatic vessels; cystic lymphangioma (CH), with huge, macroscopic lymphatic spaces; and benign acquired progressive lymphangioma, in which the lymphatic channel dissects the dense collagen bundles [ 27 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The lymphatic system is essential in organ development, growth, function, and regeneration. 26 Future studies utilizing state-of-the-art genomic, proteomic, and imaging approaches at a single-cell level will likely advance our understanding of the lymphatic system in health and in disease. In the 21st century, new diagnostic and therapeutic approaches are warranted to treat organ-specific lymphatic diseases.…”
Section: Lymphatic System In Organ Development Regeneration and Funct...mentioning
confidence: 99%
“…2 Beyond Gaspare Aselli’s anatomic description of lymphatic vessels in 1622, modern biomedical research has identified the molecular framework underlying lymphatic endothelial cell structure and function in development and disease. 3,4 In the capillary vascular bed, arterial and venous pressure gradient differences generate net fluid flux out of circulation (Ernest Starling’s equation) into the interstitium leading to interstitial fluid (lymph) accumulation. Lymphatic capillaries collect excess interstitial fluid and transport it to the subclavian vein via the thoracic duct.…”
mentioning
confidence: 99%
“…4 Developmental lymphatic malformations or structural/functional lymphatic defects secondary to diseases cause aberrant accumulation of interstitial fluid, leading to primary or secondary lymphedema. 3…”
mentioning
confidence: 99%
See 1 more Smart Citation